Inovasi Kurikulum dalam Perspektif Komponen-Komponen Kurikulum Pendidikan Agama Islam - Ahmad Wahyu Hidayat (STAI Terpadu Yogyakarta, 2020)
This study will elaborate on curriculum innovation in the perspective of PAI curriculum components. Where the curriculum can be interpreted as a variety of variations, there is a narrow view of the curriculum as a collection of subjects. As for the broad interpretations include all experiences gained by students because of the direction, guidance and responsibilities of the school. The conclusion is that a component is an integral and functional part that is inseparable from a curriculum system because the component itself has a role in the formation of the curriculum system. Because the curriculum can be likened to a human or animal organism, which has a certain anatomical arrangement. Thus, curriculum components are the parts or elements of the curriculum that have been planned to achieve certain educational goals. The curriculum can be likened to a human or animal organism, which has a certain anatomical arrangement. The main elements or components of the anatomy of the curriculum body are objectives, content or material, delivery processes or systems and media, and evaluation. These components are closely related to each other. Criticism of the writer which proposes the addition of religious values and the value of cooperation to maximize the Islamic Education curriculum in implementing it in schools.